Analisis Potensi Pergerakan Tanah Berdasarkan Ground Shear Strain Untuk Wilayah Bekasi - Rahman, Aditya Setyo; Sutiyono, Sutiyono; Wardaningsih, Kuurnia; Istofiyah, Istofiyah; Cindiwati, Cindiwati; Alfiandy, Solih (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2024)
This study analyzes the Ground Shear Strain (GSS) values and predicts earthquake vibration phenomena in the Bekasi area. The results show that the GSS values are relatively low (0.14 - 0.20), indicating a low level of vulnerability to earthquake shaking. At PGA 0.22 - 0.302 g, it is predicted that only the wave vibration phenomenon will occur (ground vibration is felt, not damaging). Despite the low vulnerability level, it is important to remain vigilant and carry out earthquake mitigation, such as building earthquake-resistant structures and preparing evacuation plans.